Teachers’ Efforts in Enhancing Students’ Motivation to Memorize the Qur’an at Tahfidzul Qur’an Islamic Boarding School, Lampung - Lailatul Hikmah; Syiamsyah Fitriyani (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
His research investigates the efforts of ustadz and ustadzah in increasing students’ motivation to memorize the Qur’an at Pondok Pesantren Tahfidzul Quran Putri Bustanul Ulum. Using a qualitative approach with observation, interviews, and participatory interaction, the study examines how these educators support and inspire their students. Guided by the question of how teachers enhance memorization motivation, the research uses the Miles and Huberman data analysis model. The findings show that personalized guidance, effective communication, and supportive teaching practices significantly improve students' motivation and engagement. These efforts not only strengthen spiritual growth but also enhance academic achievement. The study contributes to educational motivation theory and offers practical insights for Islamic education, highlighting how a nurturing environment and dedicated educators can positively shape students’ learning outcomes and personal development.